The relationship between knowledge and hypothermia first aid attitudes in mountain climbers - Mayang Dwi Setiyani; Nurul Fatwati Fitriana (Proceedings Series on Health & Medical Sciences, 2020)
Mountain climbing is an interesting and challenging activity, but it has high risks. There is a risk of harm that threat the body and safety during mountain climbing. One of the risks that can occur in mountain climbing is hypothermia which should be treated quickly and appropriately otherwise it can be life-threatening. From the results of preliminary studies that have been conducted by researchers at the Mount Prau Basecamp. According to the Gunung Prau Basecamp guard in 2017 there were 4 cases of hypothermia per week, even in 2014 there was 1 case of a climber who died due to hypothermia. This case occurred because of the climber's lack of knowledge of doing first aid to victims who had hypothermia.  In this case, the climber's knowledge and attitude about prevention and first aid when experiencing hypothermia are the most important factors.The aim of this study was to determine the correlation between climber's knowledge and hypothermia first aid attitudes on the mountain.The type of this research was quantitative research with the correlation study method and a cross-section approach. The population in this study were all climbers of Mount Prau Wonosobo with a sample of 333 respondents. The sampling technique used in this study was consecutive sampling. The data in this study were analyzed using the chi square statistical test.The results of this study were obtained from 333 respondents, 301 respondents (90.4%) had good knowledge and 297 respondents (89.2%) had good attitudes. Statistical analysis showed significant results with a p-value (0.0001) less than 0.05, thus H0 was rejected and H1 was accepted, which indicated that there was a relationship between the climber's knowledge and hypothermia first aid attitudes on the mountain. In conclusion Knowledge affects a person's attitude towards handling hypothermia. On condition that the knowledge is good, ensuingly the attitude in handling hypothermia will be good.